Flagellin-induced immune response in human-induced pluripotent stem cell-derived cardiomyocytes - Yücel, Gökhan; Zhou, Xiao-Bo; Terkatz, Linda; Wendel, Angela; Reinhardt, Julius; El-Battrawy, Ibrahim; Sattler, Katherine; Cyganek, Lukas; Utikal, Jochen; Langer, Harald; Scharf, Rüdiger Eberhard; Dürschmied, Daniel; et al. (International journal of molecular sciences, 2023)
Pathogen-associated molecular patterns (PAMPs) are involved in the pathogenesis of septic cardiomyopathy through a toll-like receptor (TLR)-mediated immune response. Human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) can reflect the innate immune abilities of cardiomyocytes. Therefore, hiPSC-CMs may provide an attractive tool with which to study PAMP-induced alterations in cardiomyocytes. HiPSC-CMs from two different healthy donors were exposed to the PAMP flagellin (FLA) at different doses and exposure times. Alterations in the expression levels of distinct inflammation-associated cytokines, intracellular inflammation pathways including TLR5 downstream signaling, reactive oxygen species levels and surface antigen composition were assessed using PCR, ELISA and FACS techniques. Higher doses of flagellin increased the expression levels of inflammation-associated cytokines like TNFα (p < 0.01) and downstream signaling molecules like caspase-8 (p < 0.05). TLR5 expression (p < 0.01) and TLR5 fluorescence proportion (p < 0.05) increased in hiPSC-CMs after prolonged FLA exposure. FLA-induced innate immune response processes in cardiomyocytes might be detectable with an hiPSC-CMs-based in vitro model.
Veröffentlicht: 11. September 2023
Gesehen am 13.11.2023